(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article deals with the formation of aquatic ecosystems in the new conditions of existence, which is an important scientific and practical task. The studies were carried out on the lakes Shurkul, Gaukkol, Adzhalikul, which have an important national economic value in the Khorezm region of Uzbekistan. It was found that with an increase in water depth, the content of phosphorus and ammonium nitrogen increases, the content of nitrate nitrogen in the surface horizon (0–70 cm) is greater than in the lower horizon. The stability of the oxygen regime and its deficiency, there are significant daily and seasonal fluctuations. It has been established that active destruction processes are going on in the reservoirs, despite the significant biogenic load.